Construction of Novel Biomass‐Based Solar Evaporator with Asymmetric Dual‐Layer Structure for Water Desalination. (13th October 2021) - Liu, Jinhua; Xu, Linqiong; Li, Yongchao; Zhao, Jingjing; Jia, Xichen; Chao, Jiabao; Lv, Bizhi; Zhao, Yongqing
Abstract: Solar desalination technology is regarded as a low‐carbon and environment‐friendly technology to address the water crisis. The current challenge is that sunlight irradiates directly the entire water body, resulting in a low photothermal conversion efficiency. Herein, a novel photothermal compound material with dual‐layer structure for solar‐steam‐generation is developed by depositing multi‐walled carbon nanotubes (MWCNTs) and carbon black nanoparticles (CB) onto a biomass reed straw (RS) skeleton. With respect to the lower layer of the resultant generator, the porous RS skeleton with open‐cell vessel channels and closed‐cell porous basic tissues can not only supply the water to the upper layer through the capillary force, but also insulate the heat transport. Additionally, the MWCNTs‐CB hybrid photothermal composite on the upper layer with large specific surface and roughness facilitates the evaporation of water by the generated heat from the absorbed solar light. The composite generator possesses an extremely high spectral absorption of ≈99% in wet state, along with a superb evaporation rate of ≈1.45 kg m −2 h −1 and photothermal conversion efficiency of ≈87.58% under one sunlight irradiation. Thus, the deposition of MWCNTs‐CB on a renewable biomass RS skeleton develops an ideal candidate generator that hold a desirable promise for applications in seawater desalination. Abstract : A multi‐walled carbon nanotubes‐carbon black/reed straw (MWCNTs‐CB/RS) solar evaporator with dual‐layer structure is developed, containing a MWCNTs‐CB solar‐absorbed layer and a RS skeleton which possesses open‐cell vessel channels as well as closed‐cell porous basic tissues for water transportation together with thermal insulation. The desirable evaporation rate and photothermal conversion efficiency of the MWCNTs‐CB/RS highlight its superiority of application in solar steam generation and desalination.